The role that financial and non-financial incentives play in motivating employees within a financial institution in Sandton - Dicko, Kelson (The IIE, 2020)
The objective of this study was to find investigate the impact of employee motivation on organisational effectiveness. The study focused on identifying the most important indicators of motivation, defining the motivation concepts and methods, and the linkage of employee motivation with an organisation’s productivity and effectiveness. In addition, suggestions to increase employees’ level of motivation and direction for further study were also discussed. To gain deeper understanding of the research topic, different motivation theory models were reviewed. However, the attention was on analysing the two motivation theories; Herzberg’s Two-Factor theory and Self-Determination Theory. A close-ended questionnaire was used as the foundation for collecting the data from the participants, which comprised of twenty customers. In addition, quantitative method was used in order to acquire data due to the fact that it is time-efficiency and cost saving. In conclusion, the study pinpointed that personal growth, and challenging tasks are most influential motivation factors for employees. Nonetheless, the research also revealed the factors that motivate employees were not the same as the factors that retain employees at work. While there might still other ways to increase employee’ level of motivation, the practice of combining both financial incentives and non-financial was proved to be the most effective.
Keywords: Financial incentives; Non-financial incentives; Employee motivation; Financial institutions; Sandton